Re: Risk Factors of Acute Kidney Injury Following Orthotopic Liver Transplantation - Zhang, Dali; Liu, Zhenwen; Feng Bi, Jing; Liu, Hongling; Gao, Yinjie (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Zhang D, Liu Z, Bi JF, Liu H, Gao Y. Re: Risk Factors of Acute Kidney Injury Following Orthotopic Liver Transplantation. Turk J Gastroenterol. 2022;33(9):809-810.